2021
DOI: 10.3390/ijerph18116045
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Quality Improvement for ST-Segment Elevation Myocardial Infarction: A Retrospective Study Based on Propensity-Score Matching Analysis

Abstract: Reducing the treatment delay by organizing delivery of care on a regional basis is a priority for improving the quality of ST-segment elevated myocardial infarction (STEMI) care. This study aimed to evaluate the impact of the combined measures on quality metrics of healthcare delivery in Suzhou. The data were collected from the National Chest Pain Center (CPC) Data Reporting Database. 4775 patients were recruited, and after propensity-score matching, 1078 pairs were finally included for analysis. We examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Variables included in the models were selected based on their physiological relevance and potential to be associated with outcomes. We initiated the model development with a crude model (no adjustment) and then added a range of covariates into the regression models based on previous studies in the literature [14,[17][18][19]. All the models were adjusted for sex, age, signs and symptoms at presentation, heart rate, blood pressure and Killip class, arrival mode, time of day of arrival, day of arrival, class of hospital, region of hospital, and accreditation status.…”
Section: Discussionmentioning
confidence: 99%
“…Variables included in the models were selected based on their physiological relevance and potential to be associated with outcomes. We initiated the model development with a crude model (no adjustment) and then added a range of covariates into the regression models based on previous studies in the literature [14,[17][18][19]. All the models were adjusted for sex, age, signs and symptoms at presentation, heart rate, blood pressure and Killip class, arrival mode, time of day of arrival, day of arrival, class of hospital, region of hospital, and accreditation status.…”
Section: Discussionmentioning
confidence: 99%
“…The system of care for STEMI patients in community hospitals, including emergency and network referral systems, plays an important role in providing appropriate and timely treatment. 8 However, despite these systems, the mortality rate remains high, and most patients still experience delayed access to treatment. Delayed transfer of STEMI patients to the catheterization room is associated with poor outcomes and high mortality.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 , 4 , 5 However, previous research has found that quality of health care services frequently falls short of basic clinical standards or QI program performance targets, with most interventions improving process quality indicators, such as drug use, but not outcome quality, especially in‐hospital mortality and major adverse cardiovascular events. 6 , 7 , 8 , 9 Broad consultation with stakeholders, particularly frontline medical staff, is crucial to understanding the gaps between “what we know” and “what we do,” especially in a complex QI program. 10 , 11 The engagement and perception of frontline medical professionals with respect to QI programs are prerequisites for successful implementation of QI interventions.…”
mentioning
confidence: 99%